IMPLEMENTASI METODE QUEUE TREE UNTUK MANAJEMEN BANDWIDTH BERBASIS HOTSPOT (STUDI KASUS: ONESNET BEKASI) - Rasim Rasim; Mugiarso Mugiarso; Joni Warta (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
It is time for the application of Bandwidth Management to be carried out on an internet network that is experiencing a growing number of users and the required bandwidth. This study aims to implement bandwidth management in Onesnet Bekasi with the provisions of the distribution of bandwidth per user with a predetermined bandwidth limit according to the needs of Onesnet clients. Uneven bandwidth allocation and the available bandwidth is very limited, causing tug of war between Internet users on the same network so that the network lags. This research uses the Network Development Life Cycle (NDLC) method, to overcome the problem of bandwidth sharing, the Queue tree method is used. The result of this research is Onesnet Bekasi users get an upload and download bandwidth limit of 4 Mbps according to the comparison through Wireshark software. Then the results of the Quality Of Service (QOS) parameter testing were obtained with a throughput of 65.0997 b/s, a delay of 0.07, a packet loss of 0%, and jitter of 5 ms.Â Keywords: Manajemen Bandwidth; Quality Of Service; Network Development Life Cycle (NDLC); Throughput; Delay